Elevated remnant cholesterol and the risk of prevalent major depressive disorder: a nationwide population-based study - Tao, Shiyi; Yu, Lintong; Wu, Ji; Yang, Deshuang; Huang, Xuanchun; Xue, Tiantian (Frontiers in Psychiatry, 2024)
BackgroundRemnant cholesterol (RC) has received increasing attention due to its association with a variety of diseases. However, comprehensive population-based studies elucidating the relationship between RC and major depressive disorder (MDD) are limited. The current study aimed to determine the association between RC and MDD in US adults.MethodsCross-sectional data of US adults with complete RC and depression information were obtained from the National Health and Nutrition Examination Survey (NHANES) 2005-2018. MDD was evaluated using the Patient Health Questionnaire (PHQ-9). Multivariate logistic regression, sensitivity analysis, and spline smoothing plot method were conducted to explore the relationship between RC and depression. The cut-off point was calculated using recursive partitioning analysis when segmenting effects emerged. The area under the receiver operating characteristic (ROC) curve (AUC), calibration curve, Hosmer-Lemeshow test, the decision curve analysis (DCA), and clinical impact curve (CIC) were employed to evaluate the performance of RC in identifying MDD. Subgroup analyses and interaction tests were performed to explore whether the association was stable in different populations.ResultsA total of 9,173 participants were enrolled and participants in the higher RC quartile tended to have a higher PHQ-9 score and prevalence of MDD. In the fully adjusted model, a positive association between RC and PHQ-9 score and MDD was both observed (β=0.54, 95% CI 0.26~0.82; OR=1.43, 95% CI 1.15~1.78). Participants in the highest RC quartile had a 0.42-unit higher PHQ-9 score (β=0.42, 95% CI 0.15~0.69) and a significantly 32% higher risk of MDD than those in the lowest RC quartile (OR=1.32, 95% CI 1.05~1.66). Spline smoothing plot analysis further confirmed the positive and non-linear association between RC and PHQ-9 and MDD. ROC analysis (AUC=0.762), the Hosmer-Lemeshow test (χ2 = 6.258, P=0.618), and calibration curve all indicated a high performance and goodness-of-fit of the multivariate model. DCA and CIC analysis similarly demonstrated a positive overall net benefit and clinical impact for the model. Subgroup analyses and interaction tests suggested that the relationship between RC and depression remained stable across subgroups and was unaffected by other factors other than diabetes, hypertension, or hyperlipidemia.ConclusionAn elevated RC is associated with a higher risk of prevalent MDD among US adults, especially in those with diabetes, hypertension, or hyperlipidemia. The present results suggested that the management of RC levels and comorbidities may contribute to alleviating the occurrence of MDD.